1981
DOI: 10.1111/j.1365-2265.1981.tb00363.x
|View full text |Cite
|
Sign up to set email alerts
|

The Opioid Control of Lh and FSH Release: Effects of a Met‐enkephalin Analogue and Naloxone

Abstract: The effect of long-acting analogue of met-enkephalin (DAMME) and naloxone on gonadotrophin secretion has been investigated in man. In menopausal women DAMME induced a progressive fall in LH to approximately 60% of basal levels at 3 h, which was blocked by naloxone; there was a smaller fall in FSH that did not attain statistical significance. However, the LHRH-induced rise in LH and FSH in young male volunteers was unaffected by pretreatment with a high-dose DAMME infusion. Naloxone infusion in young male and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
48
0
2

Year Published

1982
1982
2002
2002

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(52 citation statements)
references
References 13 publications
0
48
0
2
Order By: Relevance
“…The delayed time of onset was not unexpected since endocrine studies with DAMME in another laboratory showed a maximum effect of luteinizing hormone release at 180 minutes 19 while naloxone has its greatest effect both on prolactin release 20 and blood pressure during sleep 5 at this same time. The reason for this delay is not clear.…”
Section: Discussionmentioning
confidence: 92%
“…The delayed time of onset was not unexpected since endocrine studies with DAMME in another laboratory showed a maximum effect of luteinizing hormone release at 180 minutes 19 while naloxone has its greatest effect both on prolactin release 20 and blood pressure during sleep 5 at this same time. The reason for this delay is not clear.…”
Section: Discussionmentioning
confidence: 92%
“…Natural endogenous opioid peptides have been implicated in the suppression of hypothalamic GnRH (Grossman et al 1981). The use of naloxone (an opiate receptor blocker) stimulates the secretion of LH in women that have previously experienced hypothalamic amenorrhea.…”
Section: Discussionmentioning
confidence: 99%
“…Recently it has been found that enkephalins decrease LH and FSH levels, affecting also adenohypo physial and other hormones [8]. This effect may be transmitted via the involvement of the opiate receptors [9]. All these data suggest that testosterone administration might be ef fective in patients suffering from CH, for one can suppose that artificial augmentation of this hormone's concentration would inhibit pain reaction.…”
mentioning
confidence: 99%